2016
DOI: 10.1177/0975425316654799
|View full text |Cite
|
Sign up to set email alerts
|

Creating Inclusive Cities

Abstract: Measuring progress towards the achievement of sustainable development goals (SDGs) will substantially depend on how countries are performing in the implementation of targets under the goals. One of the key challenges lies in designing sustainability indicators. For developing countries like India, the challenge is even more complex, given the continuous tension between quality of life aspirations and commitments towards sustainable development pathways. Thus, as countries aspire for achieving SDG-11, which see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
6
0
3
Order By: Relevance
“…However, contrary to past studies, the results of this study failed to prove the association between the smart people dimension of a smart city and the citizen's quality of life. Bhattacharya et al (2015) found that inadequate citizen participation mechanisms, limited access to information and decision-making processes, disengagement of residents and initiatives not addressing community-specific needs and aspirations can lead to this outcome. Therefore, while examining the relationship between the interaction effect of smart people and citizen participation on the citizen's quality of life, the authors found a significant positive relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to past studies, the results of this study failed to prove the association between the smart people dimension of a smart city and the citizen's quality of life. Bhattacharya et al (2015) found that inadequate citizen participation mechanisms, limited access to information and decision-making processes, disengagement of residents and initiatives not addressing community-specific needs and aspirations can lead to this outcome. Therefore, while examining the relationship between the interaction effect of smart people and citizen participation on the citizen's quality of life, the authors found a significant positive relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The central focus of smart city initiatives is to prioritise ICT while aiming to draw individuals and investments to these urban areas. This, in turn, establishes a positive cycle of development and expansion, as noted by Bhattacharya et al (2015). Today, India’s urban population exceeds 35%, indicating that the country is keeping pace with urbanisation (Awasthi, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…This concept overcomes the idea of simply instituting local governments in favor of a broad territorial approach able to effectively involve all local actors. Thus, localization appears to be critical to strengthen the impacts of local governance on sustainable development and to enable comparability in each country of alignment with the pillars of the 2030 Agenda and relative performance in implementing the goals (Barnett and Parnell, 2016;Bhattacharya et al, 2016;Cavalli, 2018;. Localization of the SDGs is recognized as a means to implement the complex agenda (ASviS, 2020; ISTAT, 2020a), to overcome economic, social, and environmental challenges through coordination on state, regional, and local scales.…”
Section: Localizationmentioning
confidence: 99%
“…Indeed, it is widely accepted and reported that cities are responsible for two-thirds of greenhouse gas emissions, are the places where vulnerable populations and critical activities and infrastructure are concentrated from the perspective of climate change impacts and are affected by social challenges such as aggregation, poverty, and inequality (Bulkeley, 2019;Abdullah, 2021;EEA, 2021b). Moreover, the 2030 Agenda for Sustainable Development (United Nations General Assembly, 2015), the New Urban Agenda (United Nations, 2017), and the Green Deal (European Commission, 2019), highlight the centrality of cities and urban processes in sustainable development and green transition (Barnett and Parnell, 2016;Bhattacharya et al, 2016;. In 2015, the United Nations 2030 Agenda United Nation General Assembly, 2015) identified 17 SDGs aimed at measuring and monitoring the progress and conditions of sustainable development of countries by 169 targets and 231 indicators.…”
Section: Introductionmentioning
confidence: 99%
“…), industrialization, which in turn leads to air pollution, techniques to improve air quality, minimizing carbon emissions, monitoring water discharge, provision for reducing the traffic flow, determining routing, predicting the number of accidents on roads, measuring traffic flow, formulating traffic strategy, etc. (Bhattacharya et al , 2016). Looking at the issues being highlighted, it is required to study human–environment systems at this stage so as to control the noise variables, thereby keeping the balance between socioeconomic conditions and environmental elements undertaken (Estoque and Murayama, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%